DEVELOPMENT OF PHYSICS COMIC LEARNING MEDIA CONTEXTUAL MODEL WITH POE METHOD ON THE SUBJECT OF EFFORT AND ENERGY ON INTEREST IN LEARNING PHYSICS - Haryadi, Rudi; Fauziah, Annida (Universitas Negeri Medan, 2024)
This study aims to determine the development of learning media for contextual model physics comics with the POE method on the subject of effort and energy towards the interest in learning physics. This study uses literature study research methods (literature) from various relevant sources such as articles, books, or data to support researchers in solving the problems raised. This research method is carried out by searching for and collecting data that is relevant and by the situation. It can be used as a reference for researchers in completing this research. This study indicates that the use of comic learning media can increase students' interest in learning physics. In addition to that, by applying the POE method, it is also possible to improve students' higher-order thinking.